Incidence of Yellow Virus Disease in Chili Pepper Plants (Capsicum frutescens L.) in East Tombatu District, Southeast Minahasa Regency - Pinaria, Arthur Gehart; Rondonuwu, Frans Bernhard; Satiman, Utari (Jurnal Agroekoteknologi Terapan (Applied Agroecotechnology Journal), 2025)
The purpose of this study is to ascertain the incidence of diseases in the chili plant population in East Tombatu District, Southeast Minahasa Regency, caused by the yellow virus that affects plants in terms of area. The sample garden is at least half a hectare in size. Purposive sampling was used to choose the sample gardens, and the survey was only done once. Five subplots, one in the center of the garden and one close to each corner, were used for sampling in each chili garden (plot). The quantity of individual plants, or sample units, in each subplot. The number of samples represents 20% of the total number of plants. The findings revealed that the melompar atas garden had the highest prevalence of yellow viral disease in cayenne pepper (100%), followed by Mundung (180.91%), esandom (80%), Malam part 2 (8.80%), and jumping (141.88%). The incidence of this illness rose as the plant grew older after being planted. Further study ideas include inventorying B. tabachi hosts, inventorying gemini virus hosts, and applying natural farming to reduce cayenne pepper infections. Keywords: Yellow Virus, Incidence, Capsicum frutescens. Abstrak. Penelitian ini bertujuan untuk mengetahui keseringan penyakit yang disebabkan oleh virus kuning yang menyerang tanaman dalam aspek luasan pada populasi tanaman cabai di Kecamatan Tombatu Timur, Kabupaten Minahasa Tenggara. Kebun sampel berukuran minimal 0,5 ha. Pemilihan kebun sampel dilakukan secara purposive sampling, dan dan survei hanya dilakukan satu kali. Sampling pada setiap kebun (plot) cabe dilakukan pada lima subplot (setiap dekat sudut kebun satu plot dan satu subplot di tengah kebun).  Jumlah unit contoh (individu tanaman) per subplot. Jumlah  sampel ialah 20 % dari jumlah tanaman. Hasil penelitian menunjukkan bahwa insidensi penyakit virus kuning pada cabe rawit tertinggi terdapat di kebun melompar atas 100% diikuti oleh Mundung 180,91% esandom 80% Malam part 2 6 8,80% dan melompat 141,88% insidensi Penyakit ini makin tinggi seiring dengan makin tingginya umur tanaman sesudah tanam. Penelitian lanjutan yang disarankan ialah: inventarisasi inang-inang B. tabachi, menginventarisasi inang-inang gemini virus dan penerapan natural farming untuk mengendalikan patogen cabe rawit secara sekaligus. Kata-Kata Kunci: Virus Kuning, Insidensi, Capsicum frutescens